(untitled) (African Journal of Biomedical Research, 2021)
Abstract Substantial evidence suggests that poor intrauterine environment produced by perinatal nutritional disturbance in both humans and animals may program susceptibility offspring to chronic diseases in life. This study investigated the role of perinatal protein restriction on food intake regulation and oxidative balance in adult offspring. Twenty-four pregnant and twelve male Sprague-Dawley rats were used. They were fed either a control diet containing 20% protein or protein-restricted (PR) diet with 8% protein. The dams were given PR diet up to parturition (in-utero group, IUPR), or from birth to post-natal day 21 (lactation group, LPR) or for a period covering both groups (combined group, CPR). Control dams with control diet was run in parallel for comparison. Food intake was determined daily and body weight measured at weekly intervals. At day 128, adiponectin, leptin and neuropeptide Y (NPY) and superoxide dismutase (SOD) catalase (CAT), reduced glutathione (GSH) and malonaldehyde (MDA) were determined. Birth weight decreased significantly (p<0.01) in IUPR and CPR offspring with a significant decrease (p<0.01) in weaning weight in CPR offspring compared with CONT. There was no significant difference in (p>0.01) final body weight in all PR offspring compared with CONT. IUPR and CPR offspring fed significantly higher (p<0.01) although adiponectin level remained unchanged (p>0.01) in all PR offspring, leptin level heightened significantly (p<0.01) in IUPR and CPR offspring and significantly decreased in LPR offspring compared with CONT. NPY significantly increased (p<0.01) in LPR offspring with no significant difference (p>0.01) compared with CONT. SOD, CAT and GSH lowered significantly (p<0.01) with concomitant increase (p<0.01) in MDA level. In conclusion, it is evidenced that PPR, at critical periods of early life exposure to dietary manipulations produced hyperphagia in IUPR and CPR offspring mediated by peripheral leptin resistance and NPY-induced hypophagia in LPR offspring with diminished oxidative status. Keywords: Hypophagia, intrauterine, perinatal, protein, Sprague-Dawl